Preliminary Study in the Development of Ethnoscience-Based Learning Media for Secondary School Students - Sukmasari, Doviyatin; Ahied, Mochammad; Fikriyah, Aida; Qomaria, Nur (Indonesian Journal of Mathematics and Natural Science Education, 2023)
This study aims to examine the results of a preliminary study on the development of ethnoscience-based science learning media in the form of perceptions about the original science of the community regarding the process of making rengginang lorjuk processed from Talang Siring sea into scientific science. This research is based on the still limited reconstruction of original science that develops in society into scientific science that can be studied and used as a source of learning independently. This research is crucial to do, considering that no one has comprehensively analyzed this topic. The subject in this study was one of the residents of the Talang Siring coastal area who had a home business in the form of rengginang lorjuk production. The research method uses descriptive qualitative. The data in this study were obtained from the results of (1) interviews; (2) Observation; and (3) Documentation. The research data obtained was then analyzed in several stages, namely data reduction, data display, and concluding/verification. Based on the results of scientific studies, it can be concluded that there is a relationship between indigenous knowledge (Indigenous Knowledge) and scientific knowledge (Scientific Knowledge).